UPAYA PIMPINAN DAYAH DALAM MENINGKATKAN POTENSI SANTRI MEMBACA KITAB KUNING DI DAYAH NURUL ISLAM BAKTIYA ACEH UTARA - Faisal Dahrul Salihin (JGK (Jurnal Guru Kita), 2022)
Dayah's Leader's Effort in Increasing the Potential of Students Reading the Yellow Book in Dayah Nurul Islam North Aceh Baktiya. Islamic religious education is education whose role is very supportive in shaping each person's personality and education that can instill good moral values in everyday life. In studying the science of Islamic education, it is also necessary to have an order for the smooth teaching and learning process, in the process of learning the Yellow Book, it is also necessary to use methods/methods to achieve the desired learning objectives. The formulation of the problem in this research is how is the practice of learning the yellow book in increasing the potential of students in the Nurul Islam Dayah, what steps are taken by the Nurul Islam Dayah leaders in increasing the potential of students to read the book, and what factors support and hinder the leadership. Dayah Nurul Islam in increasing the potential of students to read books. The purpose of this study was to determine how the process of learning the book through the methods applied in the Nurul Islam era. This study used a descriptive qualitative method. The data collection techniques are through interviews, observation and documentation, The results of the study indicate that in carrying out the book learning process in order to increase the potential of students in reading books, the teacher council uses several methods, namely the lecture method, giving assignments, reading and practicing. While the supporting factors of the implementation of the lecture method, giving assignments, reading and training are the teacher in providing more directives to control students when the learning process occurs, this support from the teacher and students are very active in mastering the knowledge given by the teacher. The obstacles are the lack of cohesiveness between teachers and students and the lack of creativity in issuing ideas.